Phylogenetic Origin of Primary and Secondary Metabolic Pathway Genes Revealed by C. maxima and C. reticulata Diagnostic SNPs - do Amaral, Milena; Barbosa de Paula, Marcia Fabiana; Ollitrault, Frederique; Rivallan, Ronan; de Andrade Silva, Edson Mario; da Silva Gesteira, Abelmon; Luro, François; Garcia, Dominique; Ollitrault, Patrick; Micheli, Fabienne (Frontiers in Plant Science, 2019)
Modern cultivated Citrus species and varieties result from interspecific hybridization between four ancestral taxa. Among them, C. maxima and C. reticulata, closely associated with the pummelo and mandarin horticultural groups, respectively, were particularly important as the progenitors of sour and sweet oranges (C. aurantium and C. sinensis), grapefruits (C. paradisi) and hybrid types resulting from modern breeding programs (tangors, tangelos and orangelos). The differentiation between the four ancestral taxa and the phylogenomic structure of modern varieties widely drive the phenotypic diversity’s organization. In particular, strong phenotypic differences exist in the coloration and sweetness and represent important criteria for breeders. In this context, focusing on the genes of the sugar, carotenoid and chlorophyll biosynthesis pathways, the aim of this work was to develop a set of diagnostic single nucleotide polymorphism (DSNP) markers to distinguish the ancestral haplotypes of C. maxima and C. reticulata, and to provide information at the intraspecific diversity level (within C. reticulata or C. maxima). In silico analysis allowed the identification of 3,347 SNPs from selected genes. Among them, 1,024 were detected as potential differentiation markers between C. reticulata and C. maxima. A total of 115 SNPs were successfully developed using a competitive PCR technology. Their transferability among all Citrus species and the true citrus genera was very good, with only 0.87% of missing data. The ancestral alleles of the SNPs were identified, and we validated the usefulness of the developed markers for tracing the ancestral haplotype in large germplasm collections and sexually recombined progeny issued from the C. reticulata/C. maxima admixture gene pool. These markers will pave the way for targeted association studies based on ancestral haplotypes.